Characterization and Rietveld refinements of new dense ceramics Ba3−xSrxTb3−xCexO9 (x = 1 and 1.5) perovskites. Issue 1 (March 2020) - Su, Yali; Lu, Dayong; Wang, Shan
Abstract : Ba3− x Sr x Tb3− x Ce x O9 ( x = 1 and 1.5) ceramics (BSTC) with a relative density of 93% and a grain size distribution of 0.2–3 µ m were prepared by the mixed-oxides reaction route. The crystalline structures, microstructures, valence states, and electrical properties of two ceramics were analyzed using X-ray powder diffraction (XRPD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), electron paramagnetic resonance (EPR), and electrical measurements. Rietveld analyses of XRPD patterns show that BSTC1 is indexed as a trigonal structure with the space group R -3 c, and BSTC3/2 is indexed as an orthorhombic perovskite structure with the space group Pmcn . The EPR, XPS, and electrical conductivity results confirm that Ce and Tb ions in BSTC exist as Ce 4+ and mixed-valence states of Tb 4+ /Tb 3+, respectively. At room temperature, the two BSTC ceramics exhibit a similar semiconducting behavior. The relationships between electrical conductivity and temperature/frequency are provided. The defect chemistry is discussed.